Predicting Financial Distress : An Altman Z-Score Analysis of Logistics Companies in India - Ahamed, G. Thouseef; Ahammed, T Md. Inthiyaz (Indian Journal of Research in Capital Markets, 2024)
Logistics firms are vital to every economy or nation in today’s interconnected world since they facilitate the local or international transportation of goods and commodities. Any economy needs to estimate the financial risk connected to this industry. The research employed Altman’s Z-score model, a widely used technique in this field, to assess financial distress among 41 logistics firms that are listed on the Indian National Stock Exchange (NSE). This study gathered secondary data from the annual reports of logistics companies between 2019 and 2023 in order to calculate various ratios that are useful in determining whether or not a company is financially distressed after using the Z-score. The data for this study were analyzed using a variety of statistical techniques, including logistic regression analysis and descriptive statistics, as part of a quantitative research strategy. The studies indicated that the Altman Z-score model is a useful tool for assessing the degree of financial crisis that logistics companies listed on the Indian NSE are facing. It is possible to say that this instrument is reliable enough to predict the financial troubles of logistic enterprises, given its 96.6% accuracy rate.